PENDAPATAN USAHATANI BUAH NAGA (STUDI KASUS DI DESA ANTAP, KECAMATAN SELEMADEG, KABUPATEN TABANAN) - Sadir, Fredisius; Tariningsih, Dian; Suparyana, Pande Komang (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2019)
Consumer demand for dragon fruit in Indonesia is quite large. These needs have not been able to be fulfilled, so the opportunity to cultivate dragon fruit is still very open, both for local and international markets. The purpose of this study was to determine farming income, analyze the level of R/C ratio of farming, and find out the marketing of dragon fruit in Antap Village, Selemadeg District, Tabanan Regency. The study was conducted in Selemadeg District, Tabanan Regency, Bali in 2018. The respondents in this study using the census method, as many as 25 people. The analytical method used in this study is income analysis and marketing channel analysis. The average total cost incurred for dragon fruit farming is Rp.1,733,300/ Area. The average revenue obtained from dragon fruit farming is Rp.2,868,000.00/ Area. The average income earned is Rp.1,134,300/ Area. The results showed that the potential income of dragon fruit development in Selemadeg had good prospects because in addition to being able to reduce fruit imports and have the opportunity to penetrate the export market, it also provided high economic benefits to farmers. This is indicated by the R/C ratio analysis of dragon fruit farming at 1.65 which means it is feasible. The dragon fruit distribution channel in Antap Village goes directly to market collectors who have collaborated in the local market in the Tabanan area, and some traders around Antap Village visit the Dragon Fruit plantation directly to buy the fruit and sell it to the end consumers.